Dusun cultural tourism : reactivate Kampung Melangkap Tiong through cultural landscape design for eco-tourism - Al Malek Faseh, Amni Syauqina Hannani (2018)
Dusun culture has different characteristics that differentiate the socio-cultural landscape of the community from other tribes in Sabah. The relationship between nature and human that caused diversity in the village. This study posed about promoting the cultural activities of the Dusun ethnic at Kampung Melangkap Tiong, Kota Belud, Sabah. It will consist on elaborating the issues on environmental, physical and social context. Generously by using design approach from National Register Bulletin by NPS on landscape character give much help in evaluation and documentation process. The data collection in this study is using two methods which are primary data and secondary data as an aid to achieve the study goals. This study concern on the community needs, local distinctiveness, heritage and spatial quality for tourism. In order to sustain the image of the village and effective strategy for tourism activities, the landscape need to enhance the environment of the whole village by discovering the possibilities that can help in improving the village appearance. This study will also introduce the method to reduce the impact of the issues that exist.